2018
DOI: 10.2139/ssrn.3301143
|View full text |Cite
|
Sign up to set email alerts
|

A Journey Through the History of Commodity Derivatives Markets and the Political Economy of (De)Regulation

Abstract: The CENTER FOR DEVELOPMENT RESEARCH (ZEF) was established in 1995 as an international, interdisciplinary research institute at the University of Bonn. Research and teaching at ZEF address political, economic and ecological development problems. ZEF closely cooperates with national and international partners in research and development organizations. For information, see: www.zef.de. ZEF-Discussion Papers on Development Policy are intended to stimulate discussion among researchers, practitioners and policy make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Un marco de mayor control financiero modifica la red espacial de derivados, ya que operaciones reguladas pasan obligatoriamente por mercados bursátiles conocidos y localizados. Por el contrario, las operaciones individuales OTC facilitan la dispersión geográfica de los flujos financieros, que puede determinarse libremente en el contrato firmado entre el gestor y su contraparte, pudiendo favorecer la presencia sobredimensionada de permutas, con el peligro de reproducir una situación similar a la de 2008 (Algieri, 2018).…”
Section: Estado De La Cuestiónunclassified
“…Un marco de mayor control financiero modifica la red espacial de derivados, ya que operaciones reguladas pasan obligatoriamente por mercados bursátiles conocidos y localizados. Por el contrario, las operaciones individuales OTC facilitan la dispersión geográfica de los flujos financieros, que puede determinarse libremente en el contrato firmado entre el gestor y su contraparte, pudiendo favorecer la presencia sobredimensionada de permutas, con el peligro de reproducir una situación similar a la de 2008 (Algieri, 2018).…”
Section: Estado De La Cuestiónunclassified
“…When futures markets were developed, the quality of the goods needed to be a component of pricing, as seen in the Dojima Rice Exchange during the Edo period (1,867). The theory is that by tracking the prices both before the development of the exchange and after, it can be shown that the exchange reduced the amount of volatility in the price (Algieri, 2018). In the 1800s, the first commodities market was established in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The creation of a grading system and institution where grades could be better guaranteed had a significant impact on the price of the grain. These improvements gave confidence to farmers and investors and started futures trading based on this institutional confidence (Algieri, 2018). Price stabilization took some of the guesswork out of farming, and futures made it possible for farmers to have more predictive revenue streams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation